Polish Surnames Motivated by Appellatives in the Anthroponymicon of Lutsk (Linguostylistic Studies, 2019)
Recently, the researchers have become increasingly interested in the studies of the regional anthroponymy, including surnames as one of the most relevant and topical linguistic issues. Surnames are considered mainly as a linguistic phenomenon in terms of linguistic and historical development, with a focus on their origin, surname appelative semantics, and specifics of name-formation patterns. The characteristic features of the economic, political, and cultural life of distant ancestors are elucidated via the case study of a surname origin. The author argues that specific features of the anthroponymic system may be associated with the linguistic interactions of those peoples who have lived in the same territory for a long time.The article analyzes the Polish surnames motivated by the appelatives, which have been selected from the metric books of the State Archives of the Volyn region and act records of the birth of the Lutsk City Council. The methods of inventory, systematization, and the method of etymological analysis were used to identify the anthroponymic materials with the features specific for the Polish anthroponymy. The method of structural-semantic analysis allows the linguistic qualification of surnames according to their word-formation model. Two categories of anthroponyms are considered: surnames motivated by the personal name (nomina personalia), and surnames derived from appellations with non-personal meaning (nomina impersonalia). The key findings of the study prove that the culture of a society, in which surnames have occurred and live, is an effective way for the official identification of family in the society. The study of the anthroponymic units with a focus on their elements semantics contributes to a better understanding of the Lutsk anthroponymicon features.
Keywords: anthroponym; surname; appellative; surnames motivated by appelatives; lexical-semantic groups